Usage-evaluation study on Vancomycin among hospitalized pediatric patients: Experience from two tertiary care centers of Eastern India - Some Suvra Bose; Moutushi Das; Tonmay Barai; Subhajit Bhakta; Abhijit Das; Suhrita Paul (Indian Journal of Child Health, 2021)
Background: Vancomycin is a highly effective bactericidal antibiotic with excellent efficacy against resistant Gram-positive microorganisms. It is losing its antimicrobial efficacy due to its rampant usage in Food and Drug Administration/Centers for Diseases Control and Prevention as well as off-label clinical uses. To stop its emerging resistance, judicious use of vancomycin following antibiotic stewardship is required. Aims: This study aims to examine the rationality of vancomycin use with respect to its adherence to Hospital Infection Control Practices Advisory Committee guidelines as well as its dosing, duration, adverse effects, and final outcome. Methodology: A retrospective cross-sectional hospital record-based study was conducted at two medical colleges of Eastern India from January 1, 2020, till June 30, 2020, incorporating all admitted newborns and children till 12 years’ age who received vancomycin for any clinical conditions. However, the patients with renal diseases or incomplete history were excluded from the study. Results: A cohort of 388 patients was included of which majority of them (41.2%) were in the age group of 2–12 years and males (56.9%). Sepsis (24.2%) and pneumonia (20.8%) were the most common indications for vancomycin prescription. Overall, appropriate usage of vancomycin was found in 57.2% of patients with maximum appropriate usage which was seen among neonates (64.5%). The areas of inappropriate usage were empirical therapy in febrile neutropenia, surgical prophylaxis, treatment of coagulase-negative Staphylococcal infection, and failure to withdraw vancomycin even after negative culture report for Gram-positive organisms. The final outcome in terms of clinical improvement was seen in 72.4% of patients irrespective of appropriate/inappropriate usage. Conclusion: Monitoring vancomycin usage should be followed in institutional practice to stop the emergence of resistance of vancomycin.